SYSTEM DYNAMICS ANALYSIS FOR IMPACT OF CLOUD-BASED INFORMATION-SHARING ON SUPPLY CHAIN PERFORMANCE - Zhang, Yueran; Niu, Zhanwen; Liu, Chao; Liu, Chaochao; Hou, Kaixuan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Cloud computing has emerged as a vital tool for facilitating information-sharing and collaboration in supply chain operations. However, how the information is shared in the cloud-based supply chain has not been thoroughly investigated. Thus, adopting a system dynamics approach, this research deepens the understanding of information transmission within the supply chain by proposing a general stock and flow model and endorsing the model in an equipment manufacturing setting in China. Building upon the general model, this paper establishes a conceptual framework for cloud-based information-sharing mechanisms both within and across supply chains. The impact of cloud-based information-sharing on supply chain performance is evaluated by inventory level and customer satisfaction. The findings indicate a positive influence of information-sharing on supply chain performance. Notably, sharing information across supply chains enhances customer satisfaction to a greater extent than within the supply chain. However, it does not lead to a significant increase in inventory levels. This research expounds on the impact of information-sharing on the supply chain in quantitative forms, which is of theoretical and practical significance to the field of supply chain management.